Kepadatan Jentik Nyamuk Aedes Aegypti di Wilayah Kerja Puskesmas Gandus Kota Palembang - Habib, Muhammad; Intan Kumalasari; Diah Navianti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The high risk of dengue transmission is greatly influenced by the density of mosquito larvae which correlates with environmental conditions and community behavior. This study aims to describe the density level of Aedes aegypti mosquito larvae in the working area of the Gandus Health Center in Palembang City in 2025 through the measurement of House Index (HI), Container Index (CI), Breteau Index (BI), Larvae-Free Numbers (ABJ), and Density Figure (DF). The method used was descriptive observational with a purposive proportional random sampling technique on 100 households in three RTs. Data was collected through direct observation using checklist sheets. The results showed that the HI was 66%, CI was 44%, BI was 107%, and ABJ was only 34%, which indicates that the larval density is very high and far below the WHO standard (≥ 95%). The DF value is in the range of 7–9, reinforcing the finding of high vector density. This condition shows that the area is at high risk of dengue transmission. Interventions are needed in the form of regular mosquito nest eradication (PSN), increasing public education, and strengthening the role of jumantic cadres in sustainable vector control.